2016
DOI: 10.1038/srep37598
|View full text |Cite
|
Sign up to set email alerts
|

Growth Mechanisms of Inductively-Coupled Plasma Torch Synthesized Silicon Nanowires and their associated photoluminescence properties

Abstract: Ultra-thin Silicon Nanowires (SiNWs) were produced by means of an industrial inductively-coupled plasma (ICP) based process. Two families of SiNWs have been identified, namely long SiNWs (up to 2–3 micron in length) and shorter ones (~100 nm). SiNWs were found to consist of a Si core (with diameter as thin as 2 nm) and a silica shell, of which the thickness varies from 5 to 20 nm. By combining advanced transmission electron microscopy (TEM) techniques, we demonstrate that the growth of the long SiNWs occurred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 40 publications
1
20
0
Order By: Relevance
“…By examining the structural and morphological characteristics of the as-grown ICP-Si nanopowder, we found that three main families of Si nanostructures can be distinguished [5], as shown in figure 1: (i) cylindrical SiNWs presenting a rod-shaped Si nanocore (mean diameter of 2.7 nm), as depicted in figure 1(a); (ii) chaplet-like SiNWs featuring a chain of almond-shaped SiNCs (mean diameter of 4.5 nm) connected by a very thin Si wire (diameter of 1-2 nm), as illustrated in figure 1(b); and (iii) SiNC chains consisting of a sequence of isolated spherical Si nanocrystals (mean diameter of 7 nm) embedded in a continuous SiO 2 cylinder, as those shown in figure 1(c). The nano-crystalline nature of all these three configurations was ascertained by high-resolution TEM (HRTEM) analyses, as shown in the figures 1(d)-(f).…”
Section: Formation Of Si Nanohybridsmentioning
confidence: 99%
See 4 more Smart Citations
“…By examining the structural and morphological characteristics of the as-grown ICP-Si nanopowder, we found that three main families of Si nanostructures can be distinguished [5], as shown in figure 1: (i) cylindrical SiNWs presenting a rod-shaped Si nanocore (mean diameter of 2.7 nm), as depicted in figure 1(a); (ii) chaplet-like SiNWs featuring a chain of almond-shaped SiNCs (mean diameter of 4.5 nm) connected by a very thin Si wire (diameter of 1-2 nm), as illustrated in figure 1(b); and (iii) SiNC chains consisting of a sequence of isolated spherical Si nanocrystals (mean diameter of 7 nm) embedded in a continuous SiO 2 cylinder, as those shown in figure 1(c). The nano-crystalline nature of all these three configurations was ascertained by high-resolution TEM (HRTEM) analyses, as shown in the figures 1(d)-(f).…”
Section: Formation Of Si Nanohybridsmentioning
confidence: 99%
“…Figures 4(a)-(c) show the statistical distributions of the occurrence of the three different SiNW morphologies for the as-grown as well as the annealed ICP-SiNWs at 800 and 1200°C, respectively. It was found that the cylindrical SiNWs constitute the major component (53% of the overall population) of the as-grown sample, while the percentages of the chaplet-like SiNWs and the SiNC chains represent respectively 35% and 12% of the total nanostructures constituting the as-grown ICP-SiNWs (see figure 4(a)) [5]. When the sample was annealed at 800°C, the percentages of both cylindrical and chaplet-like SiNWs decreased to ∼44% and 32%, respectively, while the proportion of SiNC chains increased to 24% (see figure 4(b)).…”
Section: Formation Of Si Nanohybridsmentioning
confidence: 99%
See 3 more Smart Citations